Reproductive Characteristics of Pseudecheneis sulcatus (Siluriforms: Sisoridae) in the Lower Yarlung Zangbo River, Tibet - Pengcheng Lin; Huaming Hu; Zheng Gong; Jian Wang; Xin Gao (Fishes, 2023)
The present research offers novel understandings of the reproductive biology of Pseudecheneis sulcatus (McClelland, 1842) found in the Yarlung Zangbo Grand Canyon, a biodiversity hotspot. Reproductive characteristics of Pseudecheneis sulcatus, including their maturation age, fertility, spawning season, and maximum body size, constitute important aspects of its life-history traits. We collected a total of 310 specimens from the Yarlung Zangbo River’s Motuo reach between March and November 2016 and found the male-to-female ratio to be 0.73:1, markedly different from the anticipated 1:1. The total length of individuals ranged from 72 to 207 mm, while overall weight ranged from 2.5 to 65.0 g. Their length at first maturity was estimated as 131 mm in males and 132 mm in females. Based on the adult proportion and fluctuation in the monthly gonadosomatic index (GSI) and size distribution of oocytes, spawning was determined to occur from March to June. The absolute fecundity ranged between 247 and 2886 eggs, while the fluctuation in average relative fertility ranged between 16.8 and 77.1 eggs/g of fish. The fecundity of P. sulcatus was linearly correlated to the overall weight and length of the fish along with the ovarian weight. In conclusion, P. sulcatus spawned synchronously in spring and early summer, exhibiting low fecundity and large oocytes. Our results provided basic information in understanding how this species adapted well to the unique canyon environment, which may be useful for developing a sustainable conservation plan for P. sulcatus at the lower reach of the Yarlung Zangbo River.